Student mobility within the internationalization strategy of the Faculty of Law, University of Montreal - Vega Cárdenas, Yenny (2015)
Students are the foundation and the raison d'être of the universities. Provide an education with high standards of quality involves offering programs that allow students to adapt and respond adequately to the new challenges faced by an increasingly globalized society. The internationalization of education is no longer an option for Universities and has become a real imperative. Within these processes, student mobility has been identified as a factor that objectively represents the dynamism of internationalization policies implemented in an institution. The international leadership adopted by the School of Law at the University of Montreal, has allowed a large percentage of their student population being benefited from international training. In this regard, the summer schools organized in China in collaboration with the CUPL as in Costa Rica with the School of Law at the University of Costa Rica, are successful models that have contributed not only to an openness to other cultures and languages, but also to other approaches to the study of law.